2018
DOI: 10.1186/s41240-018-0087-y
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary evaluation of some aspects of the ecology (growth pattern, condition factor and reproductive biology) of African pike, Hepsetus odoe (Bloch 1794), in Lake Eleiyele, Ibadan, Nigeria

Abstract: A preliminary investigation of length-weight relationship, condition factor and reproductive ecology of African pike fish, Hepsetus odoe, was conducted between June to August 2010 in Lake Eleiyele. A total of 90 samples of the fish species were caught by fishermen using gill nets. The results obtained showed that fish species had isometric growth pattern (contrary to negative allometry expected) with the growth exponent, b value of 2.64, that is not statistically different from 3 and with high statistical powe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 77 publications
(86 reference statements)
1
16
0
Order By: Relevance
“…According to Beverton and Holt (1957), the departure of the 'b' value from three is rare in adult fishes. In our case, observed variation in the 'b' value could be attributed to several factors such as length range used, season, stomach fullness, gonadal maturity, diet, sampling gear, mesh size, fishing pressure, and presence or absence of disease and parasite (Froese, 2006;Ogunola et al, 2018). However, these factors were not considered in the present study, and thus the observed variations in LWRs parameters could be due to the effect of a single factor or synergistic effect of multiple factors.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…According to Beverton and Holt (1957), the departure of the 'b' value from three is rare in adult fishes. In our case, observed variation in the 'b' value could be attributed to several factors such as length range used, season, stomach fullness, gonadal maturity, diet, sampling gear, mesh size, fishing pressure, and presence or absence of disease and parasite (Froese, 2006;Ogunola et al, 2018). However, these factors were not considered in the present study, and thus the observed variations in LWRs parameters could be due to the effect of a single factor or synergistic effect of multiple factors.…”
Section: Discussionmentioning
confidence: 64%
“…Positive allometric growth represents that higher increment in weight as compared to length (fish becomes stouter or heavier or deeper-bodied). Negative allometric growth represents a higher increment in length as compared to weight (fish becomes slender or lighter) (Ogunola, Onada, & Falaye, 2018;Wootton, 1998). Length-weight analysis of pooled (male + female) data suggested the fish exhibited significantly higher exponents (b = 3.336) than expected under isometry (b = 3), indicating the growth of P. khavalchor in the Panchaganga River was positive allometric.…”
Section: Discussionmentioning
confidence: 98%
“…Observed variation in the “ b ” value of fishes could be attributed to several factors such as sampling site, season, sex, gonadal maturity, stomach fullness, diet, length range used, sampling gear, mesh size, frequency of sampling, fishing pressure (Froese, ; Ogunola et al, ; Pise et al, ) which were not considered in the present study. Fish with ideal growth shows the coefficient of determination ( R 2 ) between 0.90 and <1 (Hanif, Siddik, Chaklader, Pham, & Kleindienst, ).…”
Section: Discussionmentioning
confidence: 91%
“…Nevertheless, for majority of the freshwater fishes inhabiting the Western Ghats of India length–weight relationships (LWRs) data are still lacking. LWRs data of the fishes have several applications such as indirect estimation of body weight based on the body length, calculation of condition indices, and also for comparisons of species’ growth trajectories (Chen et al, ; Froese, ; Ogunola, Onada, & Falaye, ). Therefore, the present study was conducted in order to determine LWRs for nine freshwater fish species collected from six different rivers in the Western Ghats of India, so as to provide the basic data on species that are helpful in further detailed fisheries and fish biology studies.…”
Section: Introductionmentioning
confidence: 99%
“…Reproduction plays a vital role in understanding the ecology of different animals including fish (Ogunola, Onada, & Falaye, ). Survival of any of these species in various seasonally changing environments depends on the development of mechanisms that permit it to adjust physiological functions to changes in that environment (Adriaenssens, Damme, Seebacher, & Wilson, ).…”
Section: Introductionmentioning
confidence: 99%